If there is no subject: On infl uence, actors, horror, and other worries of the so-called Krakow Circle - Krupnik, Seweryn (Journal of Public Governance, 2014)
The aim of the paper is to critically review previous considerations concerning subjectivity. The author argues that subjectivity is both unnecessary and biased as an analytical category applied in order to understand the social reality. At the same time, however, the concept is indispensable as a normative reference.